Предмет: Алгебра,
автор: Аноним
Упростите выражение :)
Приложения:
Ответы
Автор ответа:
0
1) 3/( Х - 1 ) - Х - 1 = ( 3 - х( Х - 1 ) - ( Х - 1 )) / ( Х - 1 ) = ( 3 - х^2 + Х - Х + 1 ) / ( Х - 1 ) = ( - х^2 + 4 ) / ( Х - 1 ) = ( ( 2 - Х )( 2 + Х )) / ( Х - 1 )
2) х^2 + 4х + 4 = ( Х + 2 )^2
3) ( ( 2 - Х )( 2 + Х )) / ( Х - 1 ) • ( ( 1 - Х ) / ( Х + 2 )^2 ) = - ( 2 - Х ) / ( Х + 2 ) = ( Х - 2 ) / ( Х + 2 )
Ответ ( Х - 2 ) / ( Х + 2 )
2) х^2 + 4х + 4 = ( Х + 2 )^2
3) ( ( 2 - Х )( 2 + Х )) / ( Х - 1 ) • ( ( 1 - Х ) / ( Х + 2 )^2 ) = - ( 2 - Х ) / ( Х + 2 ) = ( Х - 2 ) / ( Х + 2 )
Ответ ( Х - 2 ) / ( Х + 2 )
Автор ответа:
0
Спасибо ОГРОМНЕЙШЕЕ!!! Вы просто Бог математики :D
Похожие вопросы
Предмет: География,
автор: Vitalii2007
Предмет: Українська мова,
автор: batmantimofey
Предмет: Русский язык,
автор: adilhanarj
Предмет: Математика,
автор: enny1992